2010
DOI: 10.3201/eid1608.100208
|View full text |Cite
|
Sign up to set email alerts
|

Bat Coronaviruses and Experimental Infection of Bats, the Philippines

Abstract: Virus-infected fruit bats showed no signs of clinical infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
219
1
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(231 citation statements)
references
References 18 publications
8
219
1
3
Order By: Relevance
“…Most other CoVs have been confined to single host genera, exemplified by the detection of SARS-related CoVs and several alphacoronaviruses in Rhinolophus, Myotis, Miniopterus, Nyctalus and Carollia bat hosts, including detections of closely related viruses in individual bats separated by thousands of miles (Corman et al, 2013b;Drexler et al, 2010;Tang et al, 2006). Similarly, Hipposideros betacoronaviruses from Thailand, Kenya, Nigeria and Ghana are closely related (Gouilh et al, 2011;Pfefferle et al, 2009;Quan et al, 2010;Tong et al, 2009) and the betacoronavirus HKU9 has been detected in different species of flying foxes in Africa and Asia (Anthony et al, 2013b;Lau et al, 2010b;Tao et al, 2012;Watanabe et al, 2010;Woo et al, 2007). Of note, the detection of both host-specific and -nonspecific mammalian CoVs parallels what can be observed in the avian Coronavirinae genera.…”
Section: Bats As Coronavirus Hosts Worldwidementioning
confidence: 99%
“…Most other CoVs have been confined to single host genera, exemplified by the detection of SARS-related CoVs and several alphacoronaviruses in Rhinolophus, Myotis, Miniopterus, Nyctalus and Carollia bat hosts, including detections of closely related viruses in individual bats separated by thousands of miles (Corman et al, 2013b;Drexler et al, 2010;Tang et al, 2006). Similarly, Hipposideros betacoronaviruses from Thailand, Kenya, Nigeria and Ghana are closely related (Gouilh et al, 2011;Pfefferle et al, 2009;Quan et al, 2010;Tong et al, 2009) and the betacoronavirus HKU9 has been detected in different species of flying foxes in Africa and Asia (Anthony et al, 2013b;Lau et al, 2010b;Tao et al, 2012;Watanabe et al, 2010;Woo et al, 2007). Of note, the detection of both host-specific and -nonspecific mammalian CoVs parallels what can be observed in the avian Coronavirinae genera.…”
Section: Bats As Coronavirus Hosts Worldwidementioning
confidence: 99%
“…Two primer sets were used for the detection of BtCoV; primer set for the first PCR: IN-6 primer, 5 0 -GGTTGGGAC TATCCTAAGTGTGA-3 0 and IN-7 primer, 5 0 -CCAT CATCAGATAGAATCATCAT-3 0 [14]; primer set for the second PCR: IN-6 primer and hemi-nested reverse primer, 5 0 -ATCAGATAGAATCATCATAGAGA-3 0 [15], were used for detection of the sequence in RNA-dependent RNA polymerase (RdRp) region. These primer sets are known to be able to amplify genes of the coronavirus family including BtCoV [5,8,14,[16][17][18]. To amplify the spike (S) region sequence, consensus primers were constructed using the online consensus primer design software (CoCoMo; http://www.geneknot.jp/cocomo/) with seven sequences deposited in GenBank.…”
Section: Bat Samplesmentioning
confidence: 99%
“…However, recent studies have suggested that SARS-CoV is a recombinant of bat-derived coronaviruses [3,4]. Bat coronaviruses (BtCoVs) have now been identified in China [3,4] and other countries such as USA [5], Germany [6], Kenya [7], and the Philippines [8]; however, there has been no report of BtCoV detection in Japan. Bats have also great potential as reservoirs for emerging viruses such as Ebola and Nipah [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Sendo que a primeira já é conhecidamente importante na população de morcegos e está distribuída no mundo todo (TANG et al, 2006; ;WOO et al, 2006; CARRINGTON et al, 2008;DOMINGUEZ et al, 2008;GLOZA-RAUSCH et al, 2008;TONG et al, 2009; AUGUST; MATHEWS; NUNN, 2012; CARRINGTON et al, 2008;SHIRATO et al, 2012b; ANTHONY et al, 2013; GÓES et al, 2013;LELLI et al, 2013), enquanto que a última ainda foi pouco explorada, apresentando duas descrições na China (HE et al, 2013;XIA et al, 2014) (WOO et al, 2006;DOMINGUEZ et al, 2008;GLOZA-RAUSCH et al, 2008;WATANABE et al, 2010; AUGUST; MATHEWS; NUNN, 2012;SHIRATO et al, 2012b;LELLI et al, 2013). Em relação às espécies detectadas positivas para coronavírus, embora já tenha sido descrito em morcegos da família Molossidae GÓES et al, 2013;LIMA et al, 2013) (TANG et al, 2006;GLOZA-RAUSCH et al, 2008;MISRA et al, 2009;DREXLER et al, 2010; OSBORNE et al, 2011; ANTHONY et al, 2013 A árvore filogenética realizada a partir do fragmento parcial do gene codificador da proteína S dos coronavírus (Figura 2), mostra que as amostras desse estudo formaram um grupo separado das sequências recuperadas do GenBank.…”
Section: Discussionunclassified
“…Diversos trabalhos relatam a falha na tentativa de isolamento, mesmo utilizando uma ampla diversidade de linhagens celulares (TANG et al, 2006;GLOZA-RAUSCH et al, 2008;DREXLER et al, 2010;WATANABE et al, 2010). Mesmo utilizando linhagens de células derivadas de morcegos, o isolamento não é viável e, segundo Hoffmann et al (2013), um dos possíveis fatores é a especificidade dos coronavírus com a espécie ou gênero do hospedeiro como já descrito por outros autores (GLOZA-RAUSCH et al, 2008;DREXLER et al, 2010;CORMAN et al, 2013), fato também observado neste estudo.…”
Section: Discussionunclassified